2006
DOI: 10.1007/s10527-006-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Correction of acute stress-induced disorders of hemostasis using the KVCh-NO apparatus

Abstract: The problem of stress induced disorders of hemosta sis (ischemia, acute myocardial infarction, disseminated intravascular coagulation (DIC), thromboembolia, etc.) is important for clinics and basic research in medicine. These diseases cause disability and premature death of creative adults [17].Discoordination of systems of hemorheology, immu nity, hemostasis, and homeokinesis is a pathogenic mech anism of acute stress reaction [21]. Normal functions of visceral systems and the organism as a whole depend on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…This assumption is confirmed by the absence of significant changes in the total time spent in the area of radia- tion. The exposure to a distant source of THz waves probably has little effect and directly modulates the tissues, cells, and biological molecules, which is consistent with published data [4,8,9]. Irradiation for 30 min had a strong effect on the state of experimental animals.…”
Section: Parameter Treated (Irradiated) Animalssupporting
confidence: 90%
“…This assumption is confirmed by the absence of significant changes in the total time spent in the area of radia- tion. The exposure to a distant source of THz waves probably has little effect and directly modulates the tissues, cells, and biological molecules, which is consistent with published data [4,8,9]. Irradiation for 30 min had a strong effect on the state of experimental animals.…”
Section: Parameter Treated (Irradiated) Animalssupporting
confidence: 90%
“…There was demonstrated that THz-band of nitrogen oxide occurrence that had been performed alongside with a stress agent action, prevents stress-dependent changes progressing in an antioxidant system of an organism and decreases LPO activity. This may be connected with an increase of reactivity of free endogenic nitrogen oxide or an increase of its concentration because of the influence of the THz-band of MASO of 150.176-150.664 GHz nitrogen oxide occurrence directly on NOS and their catalyzation [1,[6][7][8][9]. It should be noticed that the THz-band irradiation of nitrogen oxide occurrence had evident stress-limiting effect [5,10], because of the overconcentration of corticosterone and catecholamines as well [10].…”
Section: Discussionmentioning
confidence: 99%
“…Irradiator had been located 1.5 cm above the body of an animal. The generator radiant power was 0.7 mW, the power density that arrives at the 3 cm² skin area was 0.2 mW/cm² [9].…”
Section: Methodsmentioning
confidence: 99%
“…Immobilization stress (a single 3-h fixation of animals in the supine posture) [5] served as the model of disorders in the intravascular component of microcirculation. The animals were exposed to TFB waves at NO frequency for 15 or 30 min using a KVCh-NO generator [10].…”
Section: Methodsmentioning
confidence: 99%